NUTRIENT CONTENT OF CORN STRAW SILAGE USING LIGNOSELLULOLITIC BACTERIAL INOCULUM - E. K., Karo; Mudita, I M.; Trisnadewi, A. A. A. S. (Jurnal Peternakan Tropika, 2021)
This study aims to determine the nutrient content of corn straw silage fermented using lignocellulolytic bacteria inoculum. The research was conducted from September to October 2020 at the Sesetan Farm and the Laboratory of Animal Nutrition and Forage, Faculty of Animal Husbandry, Udayana University. The design used was a completely randomized design (CRD) consisting of six treatments, namely: fermented corn straw without lignocellulolytic bacteria inoculum as a control (JP0), corn straw fermented inoculum Bacillus substilis BR 4 LG (JP1), corn straw fermented inoculum Bacillus substilis BR 2 CL (JP2), fermented corn straw inoculum Aneurinibacillus sp. BT 4 LS (JP3), fermented corn straw inoculum Bacillus sp. BT 3 CL (JP4), fermented corn straw inoculum Bacillus sp. BT 8 XY (JP5). Each treatment had 4 replications. The variables observed were dry matter DM), organic matter (OM), crude protein (CP), crude fiber (CF), crude fat (EE) and ash. The results showed that the use of lignocellulolytic bacteria inoculum was able to increase (P<0.05) crude protein content, crude fat and inorganic matter / ash and reduce (P<0.05) crude fiber content of corn straw silage, but did not affect the dry matter content. and organic matter (P>0.05). The use of bacterial inoculum Aneurinibacillus sp. BT4LS (JP3) produced silage with the highest crude protein (P<0.05) while the use of the bacterial inoculum Bacillus substilis BR 2 CL (JP2) produced silage with the lowest crude fiber (P<0.05). Based on the results of the study, it can be concluded that the use of lignocellulolytic bacteria inoculum can increase nutrient content, especially crude protein, crude fat, and ash, as well as reduce the crude fiber content of corn straw silage.                  Key words : lignocellulolytic bacteria inoculum, corn straw, nutrient content, silage